Retention of zinc in biofortified rice and maize during processing and cooking - Talsma, Elise F.; Gallego, Sonia; Carrillo, Patricia; Londoño Hernandez, Luis Fernando; Grenier, Cécile; Palacios, Natalia (International Center for Tropical Agriculture, 2016)
Biofortification is considered a complementary strategy to reduce micronutrient deficiencies in low- and middle -income countries. Rice and maize are two sta¬ble crops commonly consumed in Latin America where zinc deficiency is com¬mon and biofortified rice and maize could potentially assist in reducing these deficiencies. Improved biofortified varieties contain higher levels of zinc, but not much is known about the effect on zinc retention or on phytate reduction when using these crops in common recipes. Also the biofortified maize contains a bet¬ter protein profile with higher concentrations of tryptophan and lysine, which could be influenced during processing.